If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 3 = -7x + 11 Reorder the terms: 3 + 5x = -7x + 11 Reorder the terms: 3 + 5x = 11 + -7x Solving 3 + 5x = 11 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 3 + 5x + 7x = 11 + -7x + 7x Combine like terms: 5x + 7x = 12x 3 + 12x = 11 + -7x + 7x Combine like terms: -7x + 7x = 0 3 + 12x = 11 + 0 3 + 12x = 11 Add '-3' to each side of the equation. 3 + -3 + 12x = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 12x = 11 + -3 12x = 11 + -3 Combine like terms: 11 + -3 = 8 12x = 8 Divide each side by '12'. x = 0.6666666667 Simplifying x = 0.6666666667
| 162=102-x | | 11x-2x^2-4=11x+4 | | 53-v=184 | | 7cos(x)=x+1 | | 8=13y+2 | | 1/X1/3 | | -5m+4=11 | | (X+4)(3-x)(2x-1)=0 | | 1/X11/3 | | 3r/4-2/35/6 | | ln(8-2x)=0 | | 1/x3 | | 170=2x+4y | | -18-64=6(1+3k) | | 6x^2-5x+1=99ft^2 | | X-4-5=-7 | | 3a+2=6a-4 | | 2x-3-2=-5 | | 48+6x+2y=496 | | 3x+12-6x=8-3x-40 | | (2x-1)(3x-1)=99ft^2 | | x^2+(k-5)x-k=0 | | 3=b/17 | | 3a+2=5-2y | | 6x-3-3=0 | | 2x+7x-9x+21x+5x=0 | | u^2-13.4u-32.56=0 | | x+10=5x+23 | | Y=.06x+2.63 | | 3(5)-4y=-27 | | -2+y=18 | | Log(2x)(x^2)=-2 |